Factors Associated With HIV Disclosure and HIV-Related Stigma Among Adolescents Living With HIV in Southwestern Uganda - Nabunya, Proscovia; Byansi, William; Sensoy Bahar, Ozge; McKay, Mary; Ssewamala, Fred M.; Damulira, Christopher (Frontiers in Psychiatry, 2020)
HIV-related stigma has been documented as one of the greatest obstacles to reducing HIV spread, engagement in HIV treatment, and poor mental health functioning among people living with HIV (PLWH). In addition, although disclosure is important for people to receive social support, the fear of stigma and discrimination prevents PLWH from disclosing their status. For children and adolescents growing up with HIV –with no opportunity for normal transition through adolescence due to stigma, it is important to identify additional family and community support systems, to improve their acceptance and health outcomes, including mental health functioning. This study examined family communication and social support factors associated with HIV disclosure and HIV-related stigma among children and adolescents living with HIV in Uganda. Baseline data from an NICHD-funded Suubi+Adherence study (N=702) were analyzed. Adolescents (10-16 years) were eligible to participate if they were: 1) HIV positive and knew their HIV status, 2) prescribed antiretroviral therapy, 3) lived within a family, not an institution, and 4) enrolled in one of the 39 health centers in the study area. Binary logistic regression and multiple regression analyses were conducted to determine family communication (frequency and level of comfort communicating with caregiver), social support (family cohesion, perceived child-caregiver support and social support from classmates, close friends, teachers and caregivers), associated with HIV disclosure, disclosure comfort, and HIV internalized and anticipated stigma. Results show that level of comfort communicating with caregiver was significantly associated with how often children discussed their HIV status with other people (OR= 0.056, 95% CI = 1.024, 1.092, p=0.001), and level of disclosure comfort ( = 0.088, 95% CI = 0.042, 0.134, p=0.000). In addition, support from within the school environment, i.e. from teachers and classmates, was uniquely associated with both HIV disclosure and HIV-related stigma. Findings point to schools as potential for implementing HIV stigma-reduction programs. In addition, programming aimed at improving HIV care and treatment outcomes for adolescents living with HIV should consider incorporating both family communication strengthening and HIV-stigma reduction strategies in their efforts, in order to improve HIV-health related outcomes, including overall mental health functioning of HIV positive adolescents.